2016
DOI: 10.1021/acs.macromol.6b01863
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Dynamics of Poly(acrylic acid) in Polyelectrolyte Complex Coacervates Studied by Spin-Label EPR Spectroscopy

Abstract: The dynamics of spin-labeled poly­(acrylic acid) (PAA) in polyelectrolyte complexes (PECs) has been studied by EPR. It has been found that the segmental mobility of the PAA in the PECs is nearly constant in the pH range 10 to 5 but decreases dramatically for pH < 5. Recently, we have studied the dynamics of spin-labeled poly­(ethylene-alt-maleic acid) (P­(E-alt-MA)) in PECs. The rotational mobility of the P­(E-alt-MA) has been observed to depend on pH, which has been related to the formation of hydrogen bonds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…In the cases in which self-consistent variable temperature experiments have been demonstrated, they have revealed Arrhenius-like dependences on temperature (4,5,32,33). Although this observation lacks a precise formal justification, it is consistent with the widely accepted belief that the motion of spin labels is connected to the diffusion of the label's parent molecule, as well as to the local viscosity of the environment.…”
Section: Introductionsupporting
confidence: 72%
“…In the cases in which self-consistent variable temperature experiments have been demonstrated, they have revealed Arrhenius-like dependences on temperature (4,5,32,33). Although this observation lacks a precise formal justification, it is consistent with the widely accepted belief that the motion of spin labels is connected to the diffusion of the label's parent molecule, as well as to the local viscosity of the environment.…”
Section: Introductionsupporting
confidence: 72%
“…On the other hand, several studies have reported that PAA-based complexes prepared under acidic conditions exhibit high salt resistances. ,, For example, Larson and co-workers pointed out that despite the p K a of PAA being ∼5–5.5 and of PAH being ∼8.5–9.3, the salt concentrations required to induce morphological transitions from precipitate to coacervate and from coacervate to solution were markedly asymmetric around pH 7 in PAA (and potassium salt of PAA)–PAH complexes, and critical KCl concentrations >3 M were required to completely dissolve the complexes; both these observations could not be explained solely by electrostatic interactions . Lappan et al reported significantly slower dynamics of PAA chains in complexes prepared under acidic conditions, suggesting stronger association of the polymer network under low pH conditions. Thus, a comprehensive study of the phase behavior of PAA–PAH under various pH conditions is required to address the inconsistencies in PAA–PAH phase behavior.…”
mentioning
confidence: 99%
“…An increase of the rotational mobility with increasing pH was also observed in previous studies about the dynamics in PECs of PDADMAC and SL‐P(E‐ alt ‐MA) as well as spin‐labeled poly(acrylic acid) (SL‐PAA). [ 12,13 ] In these studies only mixtures with ratio of n PC /(2 n PA ) = 1.5 were investigated. The low rotational mobility of the SL at low pH has been assumed to be a consequence of hydrogen bonds between polyacid chains as well as weak hydration of the non‐dissociated polyacid repeat units.…”
Section: Resultsmentioning
confidence: 99%
“…The low rotational mobility of the SL at low pH has been assumed to be a consequence of hydrogen bonds between polyacid chains as well as weak hydration of the non‐dissociated polyacid repeat units. [ 13 ] P(E‐ alt ‐MA) is a weak polyacid with two dissociation constants of p K 0 1 = 3.8 and p K 0 2 = 6.1, [ 18 ] i.e., the degree of dissociation α D is about 0.3 at pH 4 and about 0.5 at pH 5. At pH 4, the PECs are assumed to be stabilized by hydrogen bonds, because about 70% of the COOH groups are nondissociated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation